THE BENCHMARK OF INVESTOR DECISIONS TO INVEST IN THE INITIAL PUBLIC OFFERING (IPO) - Kurniawati, Diah; Sutrisno, Sutrisno (Riset Akuntansi dan Keuangan Indonesia, 2019)
This study aims to examine how the influence of benchmarks used by investors in the process of making investment decisions during the IPO. The dependent variable in this study is the investment decision while the independent variable is financial behavior bias consisting of reputation underwriter, CEO reputation, financial statements, representativeness bias, availability bias, overconfidence bias and self control bias. In research using primary data by providing questionnaires to investors who invest during the IPO. The population is investors in Yogyakarta with a sample of 100 respondents taken by purposive sampling method according to the specified criteria. Questionnaires were tested with validity and reliability tests. To test the hypothesis multiple regression analysis is used. The results of this study indicate that reputation underwriters, CEO reputation, financial statements, representativeness bias and availability bias do not affect investment decision making during the IPO process. While overconfidence bias and self control bias have a significant positive effect on investment decision making during the IPO process.